1999
DOI: 10.1002/(sici)1521-3773(19990917)38:18<2736::aid-anie2736>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

[In3(In2)3(PhP)4(Ph2P2)3Cl7(PEt3)3]- A New Molecular III/V Compound Featuring an Unusual 19-Atom Cage

Abstract: Near C(3) symmetry is displayed by the 19-atom In-P polyhedron that forms the central structural unit in the title compound (see structure), which was synthesized by reaction of InCl(3) with PEt(3) and PhP(SiMe(3))(2). In addition to In-P bonds, the cage has In-In and P-P bonds. Six terminal chloro ligands and three PEt(3) ligands surround the cluster core which itself encloses a central chloride anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The almost equidistant Ga1−P1 (2.327(2) Å) and Ga1−P2 (2.346(3) Å) bonds in 2 a agree with sum of the calculated single‐bond radii (Ga 1.24 Å; P 1.11 Å), [11] and experimentally observed Ga−P single bond lengths in LGa(O 3 SCF 3 )(PPh 2 ) (2.312(3) Å,), [12a] LGa(P 4 ) (2.340(2), 2.346(2) Å), [12b] and LGa(H)(PPh 2 ) (2.363(1) Å) [12c] . The In1−P1 (2.485(4) Å) bond in compound 2 b is slightly shorter than the In1−P2 (2.530(5) Å) bond, which agrees with the sum of the calculated single‐bond radii (In 1.42 Å; P 1.11 Å) [11] and In−P single bonds in [(2,4,6‐ t‐ Bu 3 C 6 H 2 )In‐PSi t‐ Bu 3 ] 2 (2.515(2), 2.503(2) Å), [13a] and [In 3 (In 2 ) 3 (PhP) 4 (Ph 2 P 2 ) 3 Cl 7 (PEt 3 ) 3 ] (2.53‐2.61 Å), respectively [13b] …”
Section: Resultssupporting
confidence: 81%
“…The almost equidistant Ga1−P1 (2.327(2) Å) and Ga1−P2 (2.346(3) Å) bonds in 2 a agree with sum of the calculated single‐bond radii (Ga 1.24 Å; P 1.11 Å), [11] and experimentally observed Ga−P single bond lengths in LGa(O 3 SCF 3 )(PPh 2 ) (2.312(3) Å,), [12a] LGa(P 4 ) (2.340(2), 2.346(2) Å), [12b] and LGa(H)(PPh 2 ) (2.363(1) Å) [12c] . The In1−P1 (2.485(4) Å) bond in compound 2 b is slightly shorter than the In1−P2 (2.530(5) Å) bond, which agrees with the sum of the calculated single‐bond radii (In 1.42 Å; P 1.11 Å) [11] and In−P single bonds in [(2,4,6‐ t‐ Bu 3 C 6 H 2 )In‐PSi t‐ Bu 3 ] 2 (2.515(2), 2.503(2) Å), [13a] and [In 3 (In 2 ) 3 (PhP) 4 (Ph 2 P 2 ) 3 Cl 7 (PEt 3 ) 3 ] (2.53‐2.61 Å), respectively [13b] …”
Section: Resultssupporting
confidence: 81%
“…At the other extreme, metal−metal bonding between the different centers is evident. In addition, the clusters may be either homonuclear, as with the examples cited above, or heteronuclear, for example, [PtIn 6 ] 10+ , , [GeIn 4 ] 8+ , In 4 S in [(Me 3 Si) 3 C] 4 In 4 S, In 3 I 2 in [(Me 3 Si) 3 C] 3 In 3 I 2 , Au 3 In 3 in (dppe) 2 Au 3 In 3 Cl 6 (THF) 3 (dppe = Ph 2 PC 2 H 4 PPh 2 ), and In 9 P 10 in In 9 (PPh) 4 (P 2 Ph 2 ) 3 Cl 7 (PEt 3 ) 3 . Table concentrates on compounds that have been isolated and characterized more or less reliably at ambient temperatures and so does not include naked In n clusters (2 < n ≤ 200) 134 or species such as InE 3 and InE 5 (E = P or As) belonging to the high-energy regime and as yet but thinly detailed by experiment.…”
Section: Mixed or Intermediate Valence Indium Compoundsmentioning
confidence: 99%
“…As it turns out, disproportionation occurring on thermal decomposition of the corresponding In I or In II compound has been the means of delivery of the metalloid indium cluster compounds identified so far, namely, In 8 Ar 4 (Ar = C 6 H 3 -2,6-mesityl 2 ), In 8 (Si t Bu 3 ) 6 , and In 12 (Si t Bu 3 ) 8 382 (see Table ). Disproportionation, again achieved through serendipity more than design, has also given rise to the heteronuclear clusters featured in [MeC{CH 2 NSiMe 3 } 3 In 2 ] 2 , In 9 (PPh) 4 (P 2 Ph 2 ) 3 Cl 7 (PEt 3 ) 3 , (dppe) 2 Au 3 In 3 Cl 6 (THF) 3 , and [(dppe) 2 -Au] + [(dppe) 2 Au 3 In 3 Br 7 (THF)] - (dppe = Ph 2 PC 2 H 4 PPh 2 ); it is presumably also responsible for the formation of the anion [{(Me 3 Si) 3 C} 3 In 3 Br 3 ] - , with an In 3 Br 2 core, which is a byproduct of the reaction between InBr and LiC(SiMe 3 ) 3 ·2THF in toluene . An alternative, more controlled strategy has involved mild oxidation of the tetrahedral cluster [RIn] 4 , where R = C(SiMe 3 ) 3 , by 1,2-C 2 H 4 Br 2 , AlI 3 /I 2 , or propylene sulfide to form the heteronuclear cluster compounds R 4 In 4 Br 2 , R 3 In 3 I 2 , or R 4 In 4 S, respectively.…”
Section: 4 Homonuclear or Heteronuclear Neutral Or Anionic Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Scherer, Driess, Fenske, and others2, 5, 6 concerning the studies of substituent‐free phosphorus–metal complexes,7 is one example where studies have crossed these disciplinary lines. These disciplinary boundaries have been further eroded with the studies of phosphanide and phosphanediyl clusters reported by the research groups of Fenske811 and Driess 1214. While these systems employ phosphorus atoms to link metals in complex clusters, we have targeted systems in which chains of phosphorus atoms act as metal‐linking units.…”
Section: Methodsmentioning
confidence: 99%